Syphilis in Victorian Literature and Culture : Medicine, Knowledge and the Spectacle of Victorian Invisibility /: Medicine, Knowledge and the Spectacle of Victorian Invisibility. (2017) - Pietrzak-Franger, Monika
No abstract available